(untitled) (Journal of Academic Research, 2026)
This study aimed to evaluate scatter radiation levels outside computed tomography (CT) rooms in two public diagnostic centers in Zliten, Libya, and to assessed compliance with international radiation protection standards. Measurements were performed between January and June 2024 using Geiger-Müller radiation detectors at multiple locations, including control- room windows, doors, corridors, and waiting areas. The results revealed significant radiation leakage in both centers, particularly at doors and control room observation windows. In Souq Al-Thola’tha Polyclinic the highest leakage was recorded at the door- lock opening (48.28 μSv/h) and beneath the CT- room door (27.3 μSv/h). In Naima Hospital, the highest levels were observed at the upper right edge of the control room window (20.68 μSv/h) and under the CT- room door (9.08 μSv/h). Many measured values exceeded the recommended limit for uncontrolled areas (0.08 μSv/h), indicating inadequate shielding. These findings highlight that doors and observation windows are critical points for radiation leakage due to poor sealing and insufficient shielding. Gaps beneath doors and improper installation of shielding components contributed significantly to increased exposure. The survey also identified shortcomings in staff awareness and adherence to radiation-safety practices. In conclusion, the study emphasizes the need to improve shielding design, ensure proper installation of protective materials, and implement regular monitoring and staff training. Compliance with international guidelines and with the ALARA (as Low as Reasonably Achievable) principle is essential to minimize radiation exposure and to enhance safety for healthcare workers and the public.